Proposition for teaching metaphors and idioms of Modern Greek as a foreign language - Andreou, Georgia; Galantomos, Ioannis (Investigationes Linguisticae, 2006)
The goal of this paper is to suggest potential learning material for metaphors and idioms  of Modern Greek as a foreign language based on the cognitive linguistic approach.  Teaching and learning metaphors and idioms is deemed to be quite difficult for teachers  and learners of every language and that’s why the adoption of the cognitive framework  is believed to facilitate their acquisition, since their learning according to cognitive linguistics, is not based on traditional methods such as alphabetical order or memorization  but on the discovery of deeper semantic relations on which a major part of metaphors  and metonyms of the Greek language relies on.